ANALISIS DAMPAK HUBUNGAN SOSIAL DENGAN KETAHANAN EKONOMI KELUARGA DENGAN KASUS TUBERKULOSIS: STUDY MIXED METHOD - Andy Nuriyanto (ECO-BUILD, 2026)
Background: Tuberculosis is a social and public health problem that impacts the economic resilience of families due to the length of treatment, community stigma, health status, and patient productivity. This condition requires patients, especially the Head of the Family, to strive to maintain the family economy due to direct and indirect costs including loss of employment and social status to suppress transmission and treatment. Aims: This study aims to analyse the impact of social relationships on the economic resilience of families with tuberculosis cases. Method: A mixed method design with an explanatory sequential design approach and a quantitative data sample of 96 heads of families with Tuberculosis was used in this study. Independent data variables were obtained using a family social relationship questionnaire and dependent data variables using a Family Economic Resilience questionnaire. Quantitative data analysis was carried out using the Spearman Rank test with a significance level of 0.05 followed by a qualitative test using a triangulation method sourced from in-depth interviews with 4 patients as sources Referring to the results of quantitative data analysis. Results: Most respondents have good social relationships (n = 61; 63.5%) and most have good family economic resilience (n = 74; 77.1%). Social relationships have a significant impact on family economic resilience (p-value 0.000; correlation coefficient 0.744). Conclusion: Good family social relationships positively impact family economic resilience, particularly by addressing the principles of open and focused communication, economic decision-making, and anti-stigma emotional support.